Implikasi Peraturan Mahkamah Agung No. 1 Tahun 2016 Tentang Mediasi di Pengadilan Agama Badung - Brendan Matthew Fandoe; I Nyoman Putu Budiartha; I Gusti Agung Ayu Gita Pritayanti Dinar (Jurnal Analogi Hukum, 2024)
Supreme Court Regulation or PERMA is basically a form of regulation that contains provisions that are procedural law. According to PERMA No. 1 of 2016 concerning mediation procedures in court, mediation is a way of resolving disputes peacefully, quickly, precisely and effectively, and can open wider access to the parties to the dispute to obtain a settlement of their case, and get a sense of justice. Mediation, the resolution of disputes or disputes arises more from the wishes and initiatives of the parties, so that the mediator's role is to assist them in reaching agreements. In assisting the disputing parties, the mediator is impartial. This study aims to determine the implications of Perma No. 1 of 2016 on mediation procedures in the Badung Religious Court. The presence of PERMA No. 1 of 2016 concerning Mediation procedures is intended to provide legal certainty, order and smoothness in the process of resolving a civil dispute in order to produce peace.